Bài 2: Giải phương trình và bất phương trình sau: a) |3x| = x + 6 b) (x + 1)(2x – 2) – 3 > –5x – (2x+1)( 3-x)

Question

Bài 2: Giải phương trình và bất phương trình sau:
a) |3x| = x + 6
b) (x + 1)(2x – 2) – 3 > –5x – (2x+1)( 3-x)

in progress 0
Reese 2 tháng 2021-10-19T16:44:10+00:00 2 Answers 2 views 0

Answers ( )

    0
    2021-10-19T16:45:39+00:00

     ` a)`  

    Với ` x \ge 0`

    ` => 3x = x +6`

    ` => 3x -x = 6`

    ` => 2x = 6`

    ` => x = 3` ( thỏa mãn ` x \ge 0` )

    Với ` x < 0`

    ` => -3x = x +6`

    ` => -3x – x= 6`

    ` => -4x = 6`

    ` => x=  -6/4 = -3/2` ( thỏa mãn ` x < 0` )

    Vậy ` x \in{-3/2 ; 3}`

    `b)`

    ` (x+1)(2x-2) -3 > -5x – (2x+1)(3-x)`

    ` => 2x^2 -2x +2x -2 -3 > -5x – (6x – 2x^2 + 3 – x)`

    ` => 2x^2 – 5 > -5x – 6x + 2x^2 – 3 +x`

    ` => 2x^2 -5 + 5x + 6x -2x^2 +3 – x >0`

    ` => (2x^2 -2x^2) + (6x+5x-x) – 5 + 3 > 0`

    ` => 10x -2  > 0`

    ` => 10x > 2`

    ` => x > 1/5`

    Vậy `x > 1/5`

    0
    2021-10-19T16:45:54+00:00

    Đáp án+Giải thích các bước giải:

    `a) |3x| = x + 6`

    `+) x>=0`

    `<=>3x=x+6`

    `<=>2x=6`

    `<=>x=3`(t/m)

    `+) x<0`

    `<=>-3x=x+6`

    `<=>4x=-6`

    `<=>x=-3/2`(t/m)

    Vậy` S={3;-3/2}`

    `b) (x + 1)(2x – 2) – 3 > –5x – (2x+1)( 3-x)`

    `<=>2x^2-2-3> -5x-6x+2x^2-3+x`

    `<=>2x^2-2-3+5x+6x-2x^2+3-x>0`

    `<=>10x-2>0`

    `<=>10x>2`

    `<=>x>1/5`

    Vậy `x>1/5`

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )